Systematic Review: Pemanfaatan Media Digital untuk Inovasi E-Modul Pendidikan - Maria Veronica Deno; Khaerudin Khaerudin; Dwi Kusumawardani (Jurnal Pelayanan Masyarakat, 2025)
The development of digital technology has driven the  increasing use of e-modules as interactive learning media that support  independent and collaborative learning. The integration of pedagogical approaches and multimedia technology makes e-modules increasingly adaptive and effective in developing higher-order thinking skills. This study aims to map trends in the development and utilization of e-modules through a Systematic Literature Review (SLR)  of Scopus articles published in 2020–2024. From the selection process, 20 articles were analyzed based on their pedagogical approach, as well as the media and digital platforms used. The study results show that pedagogical approaches such as Problem-Based Learning, STEM, SETS, Discovery Learning, and Guided Inquiry have been consistently proven to improve critical thinking skills, learning outcomes, and 21st-century competencies. From a technological perspective, Android and flipbook platforms are the primary choices due to their flexible access and multimedia support such as video, animation, simulations, and interactive quizzes. These findings emphasize the importance of developing systematic, pedagogically-based e-modules supported by interactive multimedia.  Further research is needed to explore the integration of AR/VR, gamification, and artificial intelligence.